KARAKTERISASI DAN SKRINING FITOKIMIA DAUN PIRDOT (Saurauia vulcani Korth.) - Kasta Gurning; Helen Anjelina Simanjuntak (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2020)
Pirdot (Saurauia vulcani Korth.) is a plant that has great potential to be developed as raw material for herbal medicines. This study aims to characterize, and phytochemical screening of  (Saurauia vulcani Korth.) leaves. Characterization carried out on the simplistic powder and ethanol extract of pirdot (Saurauia vulcani Korth.). The extraction of pirdot (Saurauia vulcani Korth.) leaves using methanol by the maceration method. Characterization of simplistic and ethanol extract carried out to determine and ensure the appropriateness of the quality standard before it was made into the preparation of a standard drug, while the phytochemical screening was an essential first step in identifying the class of bioactive compounds to direct their potential activities as raw materials in the treatment of various diseases. The simplistic and ethanol extract leaves of pirdot (Saurauia vulcani Korth.) Contain bioactive compounds such as flavonoids, saponins, tannins, and steroids/triterpenoids and ethanol, including suitable solvents in extracting the contents of all bioactive compounds contained in leaves of  pirdot simplisia (Saurauia vulcani Korth.).